Apoio e rede social no contexto urbano: percepções de mães de crianças prematuras - Almeida, Leziane Isolina Vilela (2018)
Worldwide, more and more premature babies are being born and the survival of very small babies has also increased. Prematurity is an event that affects all the family dynamics, bringing feelings of fear and insecurity, which makes the social support important resource that enable facing the crisis situation. Therefore, this study aimed to analyze the mothers´ perception of children up to 24 months of age, born premature, in terms of social support in the urban context. It is an exploratory study, with a quantitative and qualitative approach, whose sample consisted of 75 mothers, who follow up their children in a specialized outpatient clinic for children at risk. The The Medical Outcomes Study’s social support scale was used as an instrument to measure social support and, concerning the city of residence, it was used an open question about satisfaction. It was realized that mothers have a good perception of social support in all its dimensions: affective, emotional, instrumental, material and positive social interaction. Family was referred to as an important source of support, especially the parents and grandparents of the child. In the social network prevailed relations of trust with relatives and participation in religious activities. Most mothers showed satisfaction related to the city they live in, reporting potentialities and fragilities of this space. It is concluded that family was the most perceived and valued social support by the mothers who experience a premature birth. In regard to the urban context, a positive relation with the social support was evidenced, inferring a high social support, item for a healthy municipality. The access to urban health, safety and leisure facilities perceived may be elements capable of expanding the possibilities for intervention and implementation of actions and policies in Health Promotion.